Biochemical characteristics, nutrient intakes, and chronic disease risk according to the dietary fat energy ratio in middle-aged Korean: a cross-sectional study using data from the 7th (2016–2018) Korean National Health and Nutrition Examination Survey - Ga-Hyeon Jeong; Sook-Bae Kim (Korean Journal of Community Nutrition)
Objectives This study aimed to examine health-related characteristics and chronic disease risk in middle-aged Koreans based on their fat energy intake ratio. Methods We analyzed data from 7,274 Koreans aged 40–64 years using the 7th (2016–2018) Koreans National Health and Nutrition Examination Survey. Participants were classified into three groups based on their fat energy intake ratio: insufficient (< 15%), adequate (15%–30%), and excessive (> 30%). We assessed their socio-demographic characteristics; lifestyle characteristics; biochemical characteristics; quantitative and qualitative nutrient intakes, measured using dietary reference intakes for Koreans and index of nutrition quality (INQ); and chronic disease risk. Results Significant differences were observed between the groups in age, sex, income, education, and residence region. The insufficient group had the highest proportion of older adults, male, lower income, rural residents, and lower education levels. The groups differed significantly in lifestyle characteristics, with the insufficient group having the highest rates of no walking, heavy drinking, smoking, and poor subjective health perception. Biochemical characteristics in the insufficient group exhibited the lowest levels for fasting blood glucose, hemoglobin A1c, and triglycerides. Significant differences were found in both the quantitative and qualitative intake of nutrients. The insufficient group had the lowest intake of most nutrients except fiber, whereas the excessive group had the lowest fiber intake. Based on the INQ, vitamin A and Ca were the lowest in the insufficient group, and vitamin C and folic acid were the lowest in the excessive group. The risk of diabetes mellitus and metabolic syndrome was highest in the deficient group, and the risk of liver cirrhosis was highest in the excessive group. Conclusion Insufficient or excessive fat energy intake ratio negatively affects nutrient intake and chronic disease risk. Fat energy intake of 15%–30% is important for improving nutrient intake and managing chronic diseases, such as diabetes mellitus, metabolic syndrome, and liver cirrhosis. We suggest that education and an appropriate social environment are necessary to ensure this fat energy intake.